Facilitating Automated Compliance Checking in the Safety-critical Context - Castellanos Ardila, Julieth Patricia (Electronic Communications of the EASST, 2019)
In some safety-critical domains, the applicable safety standards prescribe a safety lifecycle and process-related requirements. Process plans in accordance with the prescribed requirements are essential pieces of evidence for compliance assessment with such standards. However, providing this evidence is time-consuming and prone-to-error since safety standards are large, natural language-based documents with hundreds of requirements. Besides, a company may have many safety-critical-related processes to be checked. In this paper, we propose a novel approach that combines process modeling and compliance checking capabilities to provide the analysis required to conclude whether a process model corresponds to the model with compliant states. Hitherto, our proposed methodology has been evaluated with academic examples that show the potential benefits of its use.